Implementasi Gaya Kepemimpinan Kepala Sekolah dalam Pembinaan Profesionalitas dan Kinerja Guru - Halimah, Ai Hilmi; Tafsir, Ahmad; Setiawan, Marwan (CV. Media Publikasi Profesional, 2021)
This study aims to describe the implementation of the principal's leadership style in professional development and teacher performance (research study at SDN 3 Cikedokan). This research is a qualitative research with descriptive method, the subjects in this study are the principal and teachers. The research shows that the implementation of the leadership style of the Principal of SDN 3 Cikedokan is democratic because the Principal always consults in every decision making. Principals as educators, managers, administrators, supervisors, leaders, innovators and motivators who are quite successful in fostering professionalism and teacher performance as evidenced by good teacher discipline, motivation and responsibility, namely through the stages of program planning, implementation of work plans as well as supervision and evaluation.